Nonalcoholic fatty liver disease and alcoholic liver disease: metabolic diseases with systemic manifestations - Kovalic, Alexander J.; Cholankeril, George; Satapathy, Sanjaya K. (Translational Gastroenterology and Hepatology; Vol 4 (September 2019): Translational Gastroenterology and Hepatology, 2019)
The progression of liver disease is portrayed by several common, overarching signs and symptoms. Classically, these include findings such as spider angiomata, jaundice, palmar erythema, and as cirrhosis decompensates, ascites, variceal hemorrhage (VH), hepatic encephalopathy (HE), and hepatocellular carcinoma (HCC). Aside from these universal hallmarks among cirrhotics, patients with nonalcoholic fatty liver disease (NAFLD) and alcoholic liver disease (ALD) harbor their own distinct systemic associations and manifestations. NAFLD is tightly linked to metabolic syndrome, which appears to be a driving force for a multitude of comorbidities, such as insulin resistance, cardiovascular disease, chronic kidney disease (CKD), obstructive sleep apnea (OSA), as well as increased malignancy risk. ALD also maintains a variety of comorbidities congruent with systemic effects of chronic alcohol use. These findings are highlighted by cardiovascular conditions, neuronal damage, myopathy, nutritional deficiencies, chronic pancreatitis, in addition to increased malignancy risk. While a general, guideline-driven management for all cirrhotic patients remains imperative for minimizing risk of complications, a tailored treatment strategy is useful for patients with NAFLD and ALD who entertain their own constellation of unique systemic manifestations.